Study of Cohesion and Coherence in Description Text - Nurbaiti Nurbaiti; Surastina Surastina; Hastuti Hastuti; Purna Wiratno (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2019)
The purpose of this study is to find out and describe the forms of cohesion and coherence deviations in the descriptive text of class VII students of SMPN 6 Bandar Lampung in the 2018/2019 academic year. This research method uses qualitative because cohesion and coherence deviations in the descriptive text of class VII students of SMPN 6 Bandar Lampung in the 2018/2019 school year will be explained using words and sentences clearly, firmly, and transparently in accordance with the research findings. The results of this study indicate that students' descriptive texts are full of cohesion and coherence deviations. In the aspect of cohesion, deviations can be seen from errors in using the cohesion tool in terms of release or ellipsis and the use of conjunctions. Students are not aware that a word or phrase in the text can be released but correctly. Likewise with conjunctions. In coherence, the coherence deviations found included: the use of the wrong keyword repetition, the use of inappropriate and unvarying pronouns, the use of incorrect transition words due to the student's ignorance. In addition to the errors in the coherence tools, students did not seem to focus on the topics or themes discussed so that students' description texts were found that did not meet the parallel meaning element. That is, there are several descriptive texts of students in expressing ideas that do not focus on the problem so that they deviate from the text's keywords.